Game analysis of the last five world championship in women's handball - Skoufas, D. (European Journal of Physical Education and Sport Science, 2019)
Female handball has been growing rapidly over the last decades. The development of women`s handball arises by the analysis of the data of the events of major competitions like world championships. Due to the physical development of the handball sport, the analysis of the statistics of the last five world women's handball championships constitutes a valuable tool for demonstrating the level of female handball improvement. The aim of this study was to conduct a technical analysis of women's handball characteristics which refer to technical and tactical skills and to determine factors related to the degree of improvement of the above characteristics. The main variables used to compare technical characteristics in the last five world women's handball championships were: the efficiency of attacks (TG), the efficiency of 6m position throws (6mG), the efficiency of wing position throws (WG), the efficiency of 9m position throws (9mG), the efficiency of 7m position throws (7mG), the efficiency of fast breaks throws (FB), the efficiency of break-through throws (BT), the efficiency of assist throws (A) and the efficiency of steals (S). Data where used for analysis was taken by the International Handball Federation. ANOVA were used for finding differences between participant teams in the above characteristics. The results showed that the efficiency of all characteristics improved over the years in all teams.